Historical Painting and Portraits of Independence Heroes in Colombia during the Nineteenth Century: Lack of Public Support and Importance of Private Initiatives - Santiago Robledo Páez (Historia y Sociedad, 2018)
In this article we study historical painting and portraits of founding fathers and independence heroes produced in Colombia during the 19th century. These paintings have usually been analyzed from iconographic and iconological perspectives; however, they are presented here as cultural objects that undergo specific production, diffusion, reception and appropriation processes. To shine some light on these topics, we examined different document collections from the General Archive of the Nation (Colombia) and the Historical Archive of the National Museum (Colombia), as well as the press and legislation of the time. It was found that the minimal state support of pictorial production would have discouraged the elaboration of historical paintings in Colombia. We discovered that although portrait painting was occasionally encouraged by the Government throughout the 19th century, most of the portraits were the result of private initiatives. This situation, however, didn’t prevent their exhibition in public spaces and an increase in their circulation. In conclusion, the absence of wide ranging projects for an official production of that type of paintings leads us to relativize the role of representation in the creation of Colombia’s national narrative, particularly in the National Museum.